A General-Purpose Taxonomy of Computer-Augmented Sports Systems - Cahill, Vinny; Haahr, Mads; Reilly, Sean; Barron, Peter; Moran, Kieran (IGI Global, 2009)
The area of computer-augmented sports is large and complex and spans several disciplines. This chapter presents a general-purpose taxonomy of computer-augmented sports systems, which is intended to assist researchers and designers working in this domain. Allowing systems to be classified with regard to form as well as function, the taxonomy is intended to have several uses, including serving as a clear map to aid in the understanding of the domain and as a tool to help researchers analyse the state-of-the-art by characteristics of systems. The taxonomy also offers a common vocabulary to the multidisciplinary teams that work in computer-augmented sports and can be used to identify sparsely populated regions of the domain as promising areas for future research. The authors present and demonstrate the use of the taxonomy using four example systems selected from an extensive review.
Digital Sport for Performance Enhancement and Competitive Evolution: Intelligent Gaming Technologies
Keywords: Digital sports; Computer-augmented sports; Taxonomy; Smart & Sustainable Planet